The Schooling Situation of Special Categories in the Education and Training System, Taza Province – Morocco - El-Alami, Abdelilah; El-Bazoui, Jaouad; Bouberria, Abdelouahed (Journal of Humanities & Social Sciences, 2024)
Education is the foundational cornerstone of societies, enhancing development and improving social and economic indicators, which in turn impact individuals in all aspects of life. In pursuit of achieving this goal ,Since independence, Morocco has pursued genuine development through education and educational institutions that encompass all segments of society. This historical pursuit has involved numerous reform milestones.in this context; This article examines the schooling of special categories within the education and training system in the geographical area of Taza. As an educational management that adapts the school system to recognize the right of these groups to education. throuh inventorying and tracking the situation of downloading status programmes and extrapolating to them through personal interviews with interested persons and field forms with educational frameworks in the field, which knows a local disparity in the polarization of special cases, thereby referring to the importance of raising governance and good management to achieve social justice. This study aims at highlighting the situation of teaching the special groups of the education and training system in the province of Taza as a basic entry point for the rehabilitation of human capital and achieving social development. Based on the above, the following problems can be identified: How does the process of integrating children into a special situation in the school community by providing reception structures and optimizing the possibilities for achieving a comprehensive school open to all, with the aim of rehabilitating human capital, to implement equality and equal opportunities in an effort to improve the individual and society?